An insect homolog of the vertebrate very low density lipoprotein receptor mediates endocytosis of lipophorins - Dantuma, N P; Potters, M; De Winther, M P; Tensen, C P; Kooiman, F P; Bogerd, J; Van der Horst, D J (Journal of lipid research, 1999)
A novel member of the low density lipoprotein (LDL) receptor family was identified, which is expressed in locust oocytes, fat body, brain, and midgut. This receptor appeared to be a homolog of the mammalian very low density lipoprotein receptor as it contains eight cysteine-rich repeats in its putative ligand-binding domain. When transiently expressed in COS-7 or stably expressed in LDL receptor-deficient CHO cells, the receptor mediates endocytic uptake of high density lipophorin (HDLp), an abundant lipoprotein in the circulatory compartment of insects. Moreover, in the latter cell line, we demonstrated that an excess of unlabeled HDLp competed with fluorescent labeled HDLp for uptake whereas an excess of human LDL did not affect uptake. Expression of the receptor mRNA in fat body cells is down-regulated during adult development, which is consistent with the previously reported down-regulation of receptor-mediated endocytosis of lipophorins in fat body tissue (Dantuma, N. P., M.A.P. Pijnenburg, J. H. B. Diederen, and D. J. Van der Horst. 1997. J. Lipid Res. 38: 254-265). The expression of this receptor in various tissues that internalize circulating lipophorins and its capability to mediate endocytosis of HDLp indicate that this novel member of the LDL receptor family may function as an endocytic lipophorin receptor in vivo.